Administration of anti-CD25 mAb leads to impaired α-galactosylceramide-mediated induction of IFN-γ production in a murine model - Rosalia, Rodney A; Štěpánek, Ivan; Polláková, Veronika; Šímová, Jana; Bieblová, Jana; Indrová, Marie; Moravcová, Simona; Přibylová, Hana; Bontkes, Hetty J; Bubeník, Jan; Sparwasser, Tim; Reiniš, Milan (Immunobiology, 2013)
CD4(+)CD25(+)Foxp3(+) T regulatory cells (Tregs) and CD1d-restricted invariant natural killer T (iNKT) cells are two cell types that are known to regulate immune reactions. Depletion or inactivation of Tregs using specific anti-CD25 antibodies in combination with immunostimulation is an attractive modality especially in anti-tumour immunotherapy. However, CD25 is not expressed exclusively on Tregs but also on subpopulations of activated lymphocytes. Therefore, the modulatory effects of the specific anti-CD25 antibodies can also be partially attributed to their interactions with the effector cells. Here, the effector functions of iNKT cells were analysed in combination with anti-CD25 mAb PC61. Upon PC61 administration, α-galactosylceramide (α-GalCer)-mediated activation of iNKT cells resulted in decreased IFN-γ but not IL-4 production. In order to determine whether mutual interactions between Tregs and iNKT cells take place, we compared IFNγ production after α-GalCer administration in anti-CD25-treated and "depletion of regulatory T cell" (DEREG) mice. Since no profound effects on IFNγ induction were observed in DEREG mice, deficient in FoxP3(+) Tregs, our results indicate that the anti-CD25 antibody acts directly on CD25(+) effector cells. In vivo experiments demonstrated that although both α-GalCer and PC61 administration inhibited TC-1 tumour growth in mice, no additive/synergic effects were observed when these substances were used in combination therapy.
Keywords: Forkhead Transcription Factors; Galactosylceramides; galaktosylceramidy; Tumor Burden; exprese genu; Interleukin-2 Receptor alpha Subunit; Antigens, CD1d; Gene Expression; Mice, Transgenic; Natural Killer T-Cells; Neoplasms, Experimental; forkhead transkripční faktory; Antibodies, Monoclonal; protokoly protinádorové kombinované chemoterapie; myši transgenní; ELISA; polymerázová řetězová reakce s reverzní transkripcí; NKT buňky; Heparin-binding EGF-like Growth Factor; Reverse Transcriptase Polymerase Chain Reaction; zvířata; Intercellular Signaling Peptides and Proteins; myši; antigeny CD1d; myši inbrední C57BL; Enzyme-Linked Immunosorbent Assay; Mice; Interleukin-4; tumor burden; Kaplanův-Meierův odhad; experimentální nádory; mezibuněčné signální peptidy a proteiny; Flow Cytometry; Male; Antineoplastic Combined Chemotherapy Protocols; Mice, Inbred C57BL; receptor interleukinu-2 - alfa-podjednotka; nádorové buněčné linie; monoklonální protilátky; heparin-vázající růstový faktor podobný EGF; interleukin-4; interferon gama; regulační T-lymfocyty; průtoková cytometrie; Kaplan-Meier Estimate; Animals; Cell Line, Tumor; T-Lymphocytes, Regulatory; mužské pohlaví; Interferon-gamma